Upaya Customer Service dalam Meningkatkan Service Excelent pada Bank Nagari Syariah KC Bukittinggi - Suci Aulia Fitri; Novera Martilova (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to find and provide an explanation Customer Service Efforts to Improve Excellent Service at Bank Nagari Syariah KC Bukittinggi. To find out and explain Customer Service obstacles and solutions in improving Excellent Service at Bank Nagari Syariah KC Bukitinggi. This study employed a qualitative descriptive approach in field research methodology. The findings of this study are that Customer Service at Bank Nagari Syariah KC Bukittinggi has carried out a series of important actions in an effort to improve service excellence, this includes BNFC training to improve skills and understanding of quality service. Furthermore, customer service follows strict standard operational procedures and carries out a friendly and professional service attitude, from welcoming to closing the service. All these efforts aim to ensure that customers receive superior service and feel appreciated in every interaction with Bank Nagari Syariah KC Bukittinggi. Customer Service Obstacles and Solutions in improving excellent service at Bank Nagari Syariah KC Bukittinggi, namely the lack of adequate facilities and infrastructure at Bank Nagari Syariah KC Bukittinggi. However, in facing these obstacles, Bank Nagari Syariah took effective solutions, such as setting up an efficient management system, prioritizing services for customers with urgent problems, and planning good risk management. In facing these obstacles, Bank Nagari Syariah KC Bukittinggi strives to create changes in processes, technology and resource management, so that Service Excellence is maintained.